Optimal vitamin D spurs serotonin: 1,25-dihydroxyvitamin D represses serotonin reuptake transport (SERT) and degradation (MAO-A) gene expression in cultured rat serotonergic neuronal cell lines - Sabir, Marya S. (Genes Nutr, 2018)
BACKGROUND: Diminished brain levels of two neurohormones, 5-hydroxytryptamine (5-HT; serotonin) and 1,25-dihydroxyvitamin D(3) (1,25D; active vitamin D metabolite), are proposed to play a role in the atypical social behaviors associated with psychological conditions including autism spectrum disorders and depression. We reported previously that 1,25D induces expression of tryptophan hydroxylase-2 (TPH2), the initial and rate-limiting enzyme in the biosynthetic pathway to 5-HT, in cultured rat serotonergic neuronal cells. However, other enzymes and transporters in the pathway of tryptophan metabolism had yet to be examined with respect to the actions of vitamin D. Herein, we probed the response of neuronal cells to 1,25D by quantifying mRNA expression of serotonin synthesis isozymes, TPH1 and TPH2, as well as expression of the serotonin reuptake transporter (SERT), and the enzyme responsible for serotonin catabolism, monoamine oxidase-A (MAO-A). We also assessed the direct production of serotonin in cell culture in response to 1,25D. RESULTS: Employing quantitative real-time PCR, we demonstrate that TPH-1/-2 mRNAs are 28- to 33-fold induced by 10 nM 1,25D treatment of cultured rat serotonergic neuronal cells (RN46A-B14), and the enhancement of TPH2 mRNA by 1,25D is dependent on the degree of neuron-like character of the cells. In contrast, examination of SERT, the gene product of which is a target for the SSRI-class of antidepressants, and MAO-A, which encodes the predominant catabolic enzyme in the serotonin pathway, reveals that their mRNAs are 51–59% repressed by 10 nM 1,25D treatment of RN46A-B14 cells. Finally, serotonin concentrations are significantly enhanced (2.9-fold) by 10 nM 1,25D in this system. CONCLUSIONS: These results are consistent with the concept that vitamin D maintains extracellular fluid serotonin concentrations in the brain, thereby offering an explanation for how vitamin D could influence the trajectory and development of neuropsychiatric disorders. Given the profile of gene regulation in cultured RN46A-B14 serotonergic neurons, we conclude that 1,25D acts not only to induce serotonin synthesis, but also functions at an indirect, molecular-genomic stage to mimic SSRIs and MAO inhibitors, likely elevating serotonin in the CNS. These data suggest that optimal vitamin D status may contribute to improving behavioral pathophysiologies resulting from dysregulation of serotonergic neurotransmission.